2020
DOI: 10.1016/j.corsci.2020.108597
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and thermodynamic analysis of high-temperature CO2 corrosion of carbon steel in simulated geothermal NaCl fluids

Abstract: We discuss kinetic and thermodynamic aspects of carbon steel corrosion in CO 2 -containing NaCl fluids up to 240°C. Crystalline nm-thick Fe-oxide films only form at 160°C and 240°C providing instantaneous and moderate corrosion protection. The absence of Fe-oxide at 80°C results in high initial corrosion rates until a moderately protective, but thick and porous, FeCO 3 film forms. From the metal/film interface it grows inwards by replacing ferrite with FeCO 3 . TEM reveals a precursory, likely hydrated and chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Previously, it has been suggested that FeCl + is a precursor phase originating from a homogeneous distribution of Cl − at the interface analyzed on cross sections by SEM during a dissolution process. 19 In addition, a mixture of subsets of interatomic distances from the structures for α-Fe, Fe 3 C, and FeCl 2 was quantified. These subsets of interatomic distances, including Fe 3 C and α-Fe, provide evidence for the structural damage at the interface in the beginning of the reaction.…”
Section: Synthesis Of Corrosion Sales On Carbon Steelmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it has been suggested that FeCl + is a precursor phase originating from a homogeneous distribution of Cl − at the interface analyzed on cross sections by SEM during a dissolution process. 19 In addition, a mixture of subsets of interatomic distances from the structures for α-Fe, Fe 3 C, and FeCl 2 was quantified. These subsets of interatomic distances, including Fe 3 C and α-Fe, provide evidence for the structural damage at the interface in the beginning of the reaction.…”
Section: Synthesis Of Corrosion Sales On Carbon Steelmentioning
confidence: 99%
“…Cementite (Fe 3 C) is also frequently mentioned to be present as an undissolved phase after the dissolution of α-Fe from steel to form the FeCO 3 corrosion film. , The resulting Fe 3 C phase consists of a porous network that either is in close contact or is intermingled with the FeCO 3 corrosion film. Various authors suggest that Fe 3 C increases corrosion rates because of its ability to form a galvanic connection with α-Fe, promoting local acidification. , Despite all these observations, other works have suggested a beneficial role of Fe 3 C as inductors of the “protective” FeCO 3 formation through the solubilization of α-Fe (Fe 2+ release) to form FeCO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…15 Mundhenk et al testified that Fe-oxide formation is favored over FeCO 3 with moderately protective, thick, and porous characteristics toward higher temperatures. 16 Nimmervoll et al revealed that the mass loss increased with rising temperature, and a model of the course of corrosion was proposed. 17 Adewumi et al demonstrated that the corrosion rate increased as the exposure temperature, and uniform corrosion was noted on the specimens exposed to a low temperature (25 °C), while pitting corrosion was noted on those exposed to elevated temperature (55 °C).…”
Section: Introductionmentioning
confidence: 99%
“…The research results of Aydin et al show that the open-circuit potential value of SnO 2 -coated mild steel shifted toward more positive values compared to uncoated mild steel even under high elevated temperatures . Mundhenk et al testified that Fe-oxide formation is favored over FeCO 3 with moderately protective, thick, and porous characteristics toward higher temperatures . Nimmervoll et al revealed that the mass loss increased with rising temperature, and a model of the course of corrosion was proposed .…”
Section: Introductionmentioning
confidence: 99%
“…Geothermal production fluids normally contain significant amounts of CO2 in the range of 1-2.5% by weight [20] . CO2 corrosion ("sweet corrosion") has been discussed extensively by many authors in the oil and gas field under low temperatures and low pressures [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] . High CO2 pressure accelerates the corrosion processes by lower pH and introducing significant amounts of substances (e.g., H2CO3, HCO3 -).…”
mentioning
confidence: 99%